Practical Experience of School-Based Management Development in Madrasas: A Systematic Literature Review - Virgiawan Listanto; Citra Permatasari (Universitas Islam Negeri Walisongo, 2022)
School-Based Management is a breakthrough taken by the Government of Indonesia by giving autonomy to schools to manage and make decisions in a participatory manner to improve the quality of schools. This literature review research aims to know the participants’ characteristics in the articles, the type of measurement, and school-based managementdevelopment practices in madrasah. A total of 11 articles in 2003-2022 were used to carry out this literature review taken from the Google scholar database with the help of Harzing’s Publish or Perish 8 software for data mining. The article search was done online using the keywords “School-Based Managementin Madrasah” in both English and Bahasa. The literature review results show that the participants were school committees, principals, vice principals, teachers, administration staff, students, parents, academics, and school program managers. The studies' setting is mainly in Java Island. The measurements used in the quantitative studies were questionnaires, while interview guides were used in the qualitative approach. There were mainly four points that should be underlined from reviewed articles: (1) the principal's leadership is essential in SBM to achieve school goals, (2) the teacher as SBM supporting factor must have knowledge, skills, and attitudes as well as have sufficient insight and are willing to use their potential optimally, (3) encourage the participation of school members and the community to be directly involved in providing education, and (4) needs analysis should carry out at the outset to assist planning and managing resource availability.